Regulation of neutrophil apoptosis by cytokines, pathogens and environmental stressors - Maggini, Julian (2009)
As a key component of the innate immune response, neutrophils play a major role in host protection against bacterial and fungi infections. Neutrophils are short-lived phagocytic cells and, as a first line of defense against host insult, they are rapidly and massively recruited from the circulation into inflammatory sites, where the expression of their apoptotic program can be regulated by a number of agents such as cytokines, pathogens and environmental stressors. Apoptosis of neutrophils is central to homoeostasis and the resolution of inflammation. Recent studies have highlighted the complex convergence of different pathways in the regulation of neutrophil survival. This review focuses on the mechanisms involved in the induction and regulation of neutrophil apoptosis.